(untitled) (Applied Biological Research, 2015)
The genetic parameters, trait association and path coefficient analysis between silkgland weight and its attributes of 10 silkworm genotypes were studied during spring and summer seasons of 2010-11 at TSRI, SKUAST-Kashmir (Mirgund). The genotypes exhibited wide range variability for all the traits studied. High heritabilityaccompanied by moderate to high genotypic coefficient of variation and genetic gain were observed for filament length, shell ratio, single shell weight and filament size. Correlation studies indicated that during spring season, silkgland weight showed positive and significant correlation with shell ratio, while it showed significantly negative association with silkgland somatic index, while during summer season it showed significant positive association with all the traits except silk conversion index. The silkgland attributes exhibited varied magnitude of direct effects on silkgland weight during both spring and summer season. During summer season single shell weight showed the highest direct positive effect on silkgland weight which was followed by the filament length, while during spring season, highest positive direct effect on silkgland weight was exhibited by cocoon shell percentage(3.574) and single shell weight (3.346).